Characteristics and Epidemiology of Extended-Spectrum β-Lactamase-Producing Multidrug-Resistant Klebsiella pneumoniae From Red Kangaroo, China - Wang, Xue; Kang, Qian; Zhao, Jianan; Liu, Zhihui; Ji, Fang; Li, Junbao; Yang, Jianchun; Zhang, Chenglin; Jia, Ting; Dong, Guoying; Liu, Shelan; Hu, Guocheng; et al. (Frontiers in Microbiology, 2020)
β-lactamase represents a serious challenge for treatment and public health, extended-spectrum β-lactamase (ESBL) producing Klebsiella pneumoniae clones have been increasingly reported worldwide.However, little is known about the prevalence and biological characteristics of drug-resistant strains in zoos.During a routine surveillance at in Zhengzhou zoo of China, we reported firstly that the Klebsiella pneumoniae isolate from healthy Red Kangaroos (Macropus Rufus) showed severe MDR, especially resistant to Cefuroxime Sodium (MIC, >64 μg/ml), Ceftriaxone (MIC, >8 μg/ml) and Cefepime (MIC, >64 μg/ml) and belonged to ST290. The whole genome sequencing showed that Chrome Chr-M297-1 harbored blaDHA-3, blaSHV-1, blaCTX-M-14, FosA5, dfrA3, sul3 etc., pM297-1.1(222,864bp, IncFIB(K)) carried 9 antimicrobial genes including blaCTX-M-14 , blaTEM-191, APH(3'')-Ib, APH(6)-Id and QnrS1 etc., and pM297-1.2 (225,763bp, IncFII(K)) carried 22 antimicrobial genes including blaTEM-1, blaCTX-M-3, APH(3')-Ia, AAC(3)-IIa, AAC(6')-Ib-cr, aadA16, QnrB2, QnrS1, QacEΔ1, mphA, sul1, dfrA27, etc. Traceability analysis revealed that these two plasmids are highly similar to those recovered from human clinical samples in some southern cities in Sichuan Province, China(> 99%), suggesting the spread and distribution of these plasmids in China. Furthermore, two plasmids harboring conjugal transfer genes facilitate the transmission of antimicrobial genes by conjugation with E.coli J53. Our research shows that the transmission and adaptation of Klebsiella pneumoniae producing ESBLs in zoo environment, suggesting that the zoo is gradually becoming an important potential reservoir of clinically important drug-resistant genes.Therefore, it is necessary to strengthen the monitoring of the emergence and spread of drug-resistant strains in zoo environment in captive wild animals.